2015
DOI: 10.1262/jrd.2014-084
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of temporal gene expression patterns in the developing ovary of the embryonic chicken

Abstract: Many genes participate in the process of ovarian germ cell development, while the combined action mechanisms of these molecular regulators still need clarification. The present study was focused on determination of differentially expressed genes and gene functions at four critical time points in chicken ovarian development. Comparative transcriptional profiling of ovaries from embryonic day 5.5 (E5.5), E12.5, E15.5 and E18.5 was performed using an Affymetrix GeneChip chicken genome microarray. Differential exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a RALDH2 knockdown chicken model was produced to investigate the fundamental role of RALDH2 in meiosis initiation. It was found that meiosis occurred abnormally in RALDH2 knockdown ovaries [ 44 ]. Through transcriptome analysis, we found that the meiotic-promoting-related genes STRA8 and RALDH2 began to be significantly up-regulated in the PGCs of both breeds of chicken at the E14 stage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a RALDH2 knockdown chicken model was produced to investigate the fundamental role of RALDH2 in meiosis initiation. It was found that meiosis occurred abnormally in RALDH2 knockdown ovaries [ 44 ]. Through transcriptome analysis, we found that the meiotic-promoting-related genes STRA8 and RALDH2 began to be significantly up-regulated in the PGCs of both breeds of chicken at the E14 stage.…”
Section: Discussionmentioning
confidence: 99%
“…From embryonic Day 12.5, Stra8 is expressed in the cortex of the left ovary (Smith et al, ). Retinoic acid and RALDH2 are required for induction of meiosis initiation in ovarian germ cells in the chicken embryo (Yu et al, ), in such a way that addition of exogenous RA can rescue the inhibitory effect on meiosis in Raldh2 knockdown ovaries (Yu, Xu, Yu, Yu, & Du, ). In chicken, unlike mammals, RALDH2 is expressed in the embryonic gonads instead of the mesonephros.…”
Section: Introductionmentioning
confidence: 99%